Synthesis of active cytokinins mediated by LONELY GUY is associated with cell production during early fruit growth in peach [Prunus persica (L.) Batsch] - Sutton, Mary; Roussel, Bayleigh; Chavez, Dario J.; Malladi, Anish (Frontiers in Plant Science, 2023)
Early fruit growth in peach is characterized by cell production. Cytokinins have established roles in regulating cell division and may regulate cell production during early fruit growth. However, the role of active cytokinins and regulation of their metabolism are not well characterized in the peach fruit. In this study, fruit growth parameters, concentrations of active cytokinin bases and a cytokinin riboside, and expression of three key cytokinin metabolism-related gene families were determined during early fruit growth. Early fruit growth was associated with intensive cell production until around 40 days after full bloom. During the early stages of this period, trans-zeatin (tZ), isopentenyladenine (iP), dihydrozeatin (DHZ) and tZ-riboside (tZR), displayed higher abundance which declined rapidly by 3.5- to 16-fold during the later stages. Changes in concentration of active cytokinin bases were consistent with roles for them in regulating cell production. Expression analyses of members of cytokinin biosynthesis-related gene families, ISOPENTENYL TRANSFERASE (IPT) and LONELY GUY (LOG), further indicated that mechanisms of synthesis of cytokinin metabolites and their activation are functional within the fruit pericarp. Changes in expression of multiple members of the LOG family paralleled changes in active cytokinin concentrations. Specifically, transcript abundance of LOG3 and LOG8 were correlated with concentrations of tZ, and iP and DHZ, respectively, suggesting that the direct activation pathway is an important route for active cytokinin base synthesis during early fruit development. Transcript abundance of two CYTOKININ OXIDASE (CKX) genes, CKX1 and CKX2, was consistent with roles in cytokinin catabolism during later stages of early fruit growth. Together, these data support a role for active cytokinins synthesized in the fruit pericarp in regulating early fruit growth in peach.